1999
DOI: 10.1108/00035599910273331
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and EIS tests for anticorrosive paints pigmented with ecological pigments

Abstract: Substitution of zinc chromate or zinc yellow, traditionally used as anticorrosive pigment, for other phosphate‐based pigments that are not hazardous to health and have the same anticorrosive behaviour or even better, is studied in this paper. Four alkyd paints were specially prepared; two of them contained calcium acid phosphate or micronised zinc phosphate as anticorrosive pigments respectively. A paint containing zinc chromate was used as reference and a paint without anticorrosive pigments was used as a bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The most significant applications of phosphates are the waterborne dispersion or emulsion coatings. [4][5][6][7][8] Phosphates and their modifications have been successful in the gaining of market share due to their low cost, reduced risks (in comparison with those of lead and chromium compounds), and easy application (in comparison with other lead-and chromate free corrosion inhibitors). 9 The use of zinc phosphate instead of zinc chromate has been often recommended for the formulation of environmentally compatible anticorrosive priming compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant applications of phosphates are the waterborne dispersion or emulsion coatings. [4][5][6][7][8] Phosphates and their modifications have been successful in the gaining of market share due to their low cost, reduced risks (in comparison with those of lead and chromium compounds), and easy application (in comparison with other lead-and chromate free corrosion inhibitors). 9 The use of zinc phosphate instead of zinc chromate has been often recommended for the formulation of environmentally compatible anticorrosive priming compositions.…”
Section: Introductionmentioning
confidence: 99%
“…from the panel as a result of heating at 2008C. When a sample's potential reaches corrosion potential 2650 mV, development of corrosion on the coating/metal substrate will result (Kendig and Leidheiser, 1976;Hernandex et al, 1999). This result has been supported by the EIS study of the pure acrylic resins where the R c value have decreased in the order of 10 3 to 10 4 V shown as shown in Tables I and II. The sample heated at 2008C with 20 per cent S in 80 per cent A as shown in Figure 5 shows a similar trend in reaching the corrosion potential.…”
Section: Resultsmentioning
confidence: 65%
“…When the resistance values fall in the region of 10 1 to 10 2 V probable "coating-deficient" areas were present in the coated steel substrate. These coating-deficient areas are sites of direct contact between the electrolyte and the steel substrate (Hernandex et al, 1999). It has also been suggested that if the resistance of the coating decreases to the value of 10 3 V or below, the coating has been penetrated by the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few number of variables are taken into account in these tests (presence of aggressive ions, high humidity, high temperature, etc.) and, as a consequence, there is not a good correlation between results from these tests and the degradation the coating will suffer under service conditions [15][16][17]. In this sense, results from outdoor long exposure tests are more reliable because all variables are present and acting together during the exposure period in order to determine coating deterioration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The variation of these parameters, as a function of the immersion time, gives information about the coating deterioration process [21]. However, these accelerated tests are carried out in immersed conditions and the results are, then, applied to the behavior of the painted metal in a given atmosphere so, it is hard to find out a strict correlation between both type of tests although trends may be predicted [15][16][17]22,23].…”
Section: Introductionmentioning
confidence: 99%